Brominated flame retardants in Chinese air before and after the phase out of polybrominated diphenyl ethers. (September 2015) - Li, Wen-Long; Qi, Hong; Ma, Wan-Li; Liu, Li-Yan; Zhang, Zhi; Mohammed, Mohammed O.A.; Song, Wei-Wei; Zhang, Zifeng; Li, Yi-Fan
Abstract: Brominated flame retardants (BFRs), including polybrominated diphenyl ethers (PBDEs) and novel non-BDE flame retardants (NBFRs), were analyzed in Chinese air during China's POPs Soil and Air Monitoring Program Phase I (SAMP-I) and Phase II (SAMP-II). The levels of Σ12 PBDEs and Σ6 NBFRs in urban sites were significantly higher than those in rural sites and background sites. The higher detection rate and concentrations of high molecular weight PBDEs and NBFRs in Phase II indicated the changing of the commercial pattern of BFRs after the phase out of PBDEs in China. Temperature was the major factor affecting the seasonal variations of molecular weight BFRs in atmosphere. A significant correlation between BFRs concentration and gross domestic product (GDP) was observed, with the GDP parameter explained 59.4% and 72.7% of the total variability for Octa-BDEs and low molecular weight NBFRs, respectively. Our findings indicated an evolving commercial usage of BFRs from SAMP-I to SAMP-II, i.e. shifting from lower molecular weight to higher molecular weight congeners in China. Highlights: Twelve PBDEs and six NBFRs were investigated in Chinese air. The distribution of BFRs showed a typical primary fractionation pattern. Temperature and GDP ware the major factors affecting the levels of BFRs. An evolving commercial usage of BFRs was found since the phase out of PBDEs.